Obtenção de blenda biodegradável PLA: amido para a incorporação do micronutriente manganês - Malafatti, João Otávio Donizette (Universidade Federal de São Carlos, 2016)
The incorporation of particulate fertilizers in polymeric fibers aims to release these active principles from a substrate with a high surface area and biodegradable and biocompatible properties. It also seeks to provide the release thereof, and minimize the effects of leaching, increasing the efficiency of absorption by the roots in direct soil application. Thus, the present study was to interest obtaining a composite biodegradable matrix of acid poly -L- lactic (PLA):starch in the form of fibers, impregnating particulate solids that can act as sources of manganese ions. It is also aimed to assess any improvement in the release of the Mn2+ ions in an aqueous medium by means of variations in the processing of biodegradable blends. PLA fibers were obtained employing the electrospinning method, various solvent systems primarily been studied for obtaining a polymer solution, in order to obtain the best morphological characteristics for the support, such as control of the fiber diameter and porosity. Then there was the addition of different concentrations of starch in order to find the best embodiment of this condition to the fibers. Finally, we performed the inclusion of MnO, MnO2, MnCO3 and MnSO4, to act as sources of manganese ions, in order to observe possible and different interactions of these with the polymer matrix. In the release test, the same concentration of manganese ions 12.5% (w/v) was added experimentally to a medium extractant citric acid 2 % (w/ w) at 25 ° C in a range of 6 days for all the aforementioned precursors. It was observed that the presence of starch in the PLA fiber increased water vapor permeability (WVP) which promotes the degradation of the blend. The incorporation of salts and oxides in the blends PLA:starch used by the process resulted in different effects of the merger, agglomeration and dispersion in the composite due to its grain size and dispersive characteristics in the solvents used. The behavior of salts and manganese oxides embedded in composite promoted the rapid and direct release of assets. The composites PLA:starch is a polymeric support with high surface area which minimizes the effects of leaching allowing direct release of different precursors ion Mn2 + as fertilizer sources.
Obtaining biodegradable blend PLA:starch for the incorporation of micronutrient manganese
Keywords: Blenda; PLA; Amido; Eletrofiação; Electrospinning; Starch; Blend; CIENCIAS EXATAS E DA TERRA::QUIMICA::FISICO-QUIMICA